2001
DOI: 10.1074/jbc.m108943200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Posttranslational Formylglycine Formation by Luminal Components of the Endoplasmic Reticulum

Abstract: C ␣ -formylglycine is the key catalytic residue in the active site of sulfatases. In eukaryotes formylglycine is generated during or immediately after sulfatase translocation into the endoplasmic reticulum by oxidation of a specific cysteine residue. We established an in vitro assay that allowed us to measure formylglycine modification independent of protein translocation. The modifying enzyme was recovered in a microsomal detergent extract. As a substrate we used ribosome-associated nascent chain complexes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 26 publications
1
35
0
3
Order By: Relevance
“…Plasma mass spectrometry indicated that FGE monomers contain one or two Ca 2ϩ ions. Earlier studies, in which the activity of a crude FGE preparation was monitored with the help of an in vitro translated sulfatase polypeptide, Ca 2ϩ was shown to stimulate FGE activity up to 2.5-fold with a maximum at 15 M Ca 2ϩ (16). The activity of purified FGE was affected neither by treatment with EDTA/EGTA nor by addition of Ca 2ϩ , indicating that free Ca 2ϩ is not critical for catalytic activity; instead it may be tightly bound and fulfill a structural function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma mass spectrometry indicated that FGE monomers contain one or two Ca 2ϩ ions. Earlier studies, in which the activity of a crude FGE preparation was monitored with the help of an in vitro translated sulfatase polypeptide, Ca 2ϩ was shown to stimulate FGE activity up to 2.5-fold with a maximum at 15 M Ca 2ϩ (16). The activity of purified FGE was affected neither by treatment with EDTA/EGTA nor by addition of Ca 2ϩ , indicating that free Ca 2ϩ is not critical for catalytic activity; instead it may be tightly bound and fulfill a structural function.…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotes, FGly formation occurs in the endoplasmic reticulum (ER) and is a late cotranslational or early posttranslational oxidation of a specific cysteine residue (5,6,16). This oxidation is directed by a conserved sequence motif downstream of the cysteine to be modified (CX-PSRXXX(L/M)TG(R/K/L) in human sulfatases, see Ref.…”
mentioning
confidence: 99%
“…As this study included only four different 35 S methionine/cysteine for 1 h and chased for 6 h in label-free medium. FGE was immunoprecipitated from cells and medium, and quantified by densitometry after SDS-PAGE and phosphorimaging.…”
Section: Discussionmentioning
confidence: 99%
“…All FGE proteins localized to the ER (Table 3), thereby fulfilling one important precondition for function, as generation of FGly is a posttranslational modification of nascent, yet unfolded, sulfatase proteins inside the ER. 17,35 Nevertheless, we cannot exclude that the ER localization of defective FGE proteins just mimics a correct localization and in fact is mainly caused by the quality control mechanism inside the ER. 36,37 Importantly, the four studied FGE variants with single substitutions were more (p.G247R, p.G263V and p.R345C) or less (p.S155P) efficient in passing this quality control mechanism, as these proteins were also secreted -just like wt FGE (Figures 1, 2 and 4), which is secreted even at normal expression levels.…”
Section: Molecular Phenotype Of Msd: Differential Functional Impairmementioning
confidence: 99%
“…By contrast, the N-terminal extension was not required for in vitro FGly-generating activity of purified secreted ⌬72-FGE. However, this in vitro activity is dependent on the presence of the reductant DTT (26,32). To assess the physiological consequence of the N-terminal truncation by furin on the function of FGE, we analyzed the FGly-generating activity of the processed and the unprocessed forms of secreted FGE in the presence of GSH, a physiological reductant, or DTT serving as a control.…”
Section: Processing Of the N Terminus Leads To Inactivation Of Fge-mentioning
confidence: 99%